STUDI DESKRIPTIF KESIAPAN KERJA PESERTA DIDIK DI SMK NEGERI CIHAMPELAS - Nova Karlina; Heris Hendriana; Ecep Supriatna (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
Work readiness is a person's condition including physical, mental and experience maturity marked by the ability and willingness to carry out an activity at work. Students if they have work readiness can be absorbed in the world of work and have good work motivation. The method used is a descriptive method with a quantitative approach and the subjects in this study were students of SMK Negeri Cihampelas, West Bandung City. Determination of the sample size taken using the Slovin formula as many as 132 students. The data collection technique used in this study is proportional random sampling, it is intended that each population in the class can be represented. To obtain objective and scientifically accountable data, the collection method The data used is a job readiness questionnaire that has been tested for 48 items. The results showed that the work readiness of students was in the medium category. Where those who have work readiness are in the medium category of 68.94% (91 students), participants with high motivation are 16.67% (22 students) while students with low categories are 14.39% (19 students). It was concluded that most students had good work readiness, such as having logical and objective considerations, the ability and willingness to work, having the courage to take responsibility, the ability to adapt to the environment, especially the work environment.Keywords: : Work Readiness, Students, Vocational